2021
DOI: 10.1108/sjme-11-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

Engaging consumers through firm-generated content on Instagram

Abstract: Purpose The purpose of this paper is to analyse the impact of consumers’ perceptions of the enjoyment and originality of firm-generated content (FGC) posted on Instagram on affective customer engagement (CE). In addition, an examination is undertaken of affective CE as a driver of customer behaviour. Design/methodology/approach The paper takes a quantitative approach using a sample of 334 women followers of an eco-friendly restaurant Instagram account. After validation of the measurement scales, the hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 107 publications
3
21
0
4
Order By: Relevance
“…Finally, the relationship between satisfaction and eWOM recommendation intention was strong and significant (Figure 1), supporting H 4 . In line with previous studies, the satisfaction generated in a technological experience affects users' recommendation intentions (Ballester et al, 2021;Casaló et al, 2017Casaló et al, , 2021. The results also revealed significant indirect effects on eWOM recommendation intention through satisfaction for perceived entertainment (coeff.…”
Section: Analysis and Discussion Of Studysupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, the relationship between satisfaction and eWOM recommendation intention was strong and significant (Figure 1), supporting H 4 . In line with previous studies, the satisfaction generated in a technological experience affects users' recommendation intentions (Ballester et al, 2021;Casaló et al, 2017Casaló et al, , 2021. The results also revealed significant indirect effects on eWOM recommendation intention through satisfaction for perceived entertainment (coeff.…”
Section: Analysis and Discussion Of Studysupporting
confidence: 90%
“…In the context of AR technologies, Jung et al (2015) noted that users' satisfaction with their experiences fostered their willingness to recommend the technologies to others. This effect has been found also with SNs (Ballester et al, 2021;Casaló et al, 2021;Javornik et al, 2020). Therefore, users' satisfaction with their AR filter experiences will encourage them to recommend these tools to others:…”
Section: Sourcementioning
confidence: 68%
“…However, it should be noted that previous FGC studies have reported mixed results. Indeed, prior research has found FGC (including highly visual elements, such as Instagram posts) to positively influence visit (Ballester et al , 2021) and purchase intentions (Poulis et al , 2019) but to negatively impact the purchase intentions of new clients (Santiago et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…To managers, we would stress the importance of the pictorial element, which tends to attract initial attention, possibly via a bottom-up mechanism. This is especially important as the features of visual content tend to influence several consumer–company behavioral responses (Ballester et al , 2021). Moreover, the restaurant would be in complete control of the pictorial element.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic Word Of Mouth pada social media dapat menciptakan perilaku positif atau negatif konsumen kepada sebuah produk. Peningkatan pemasaran digital menjadikan komunikasi E-WOM dapat berpengaruh terhadap sikap yang ditunjukan oleh konsumen (Ballester et al, 2021). Konten video review produk kosmetik halal sangat berguna bagi konsumen mengetahui informasi secara detail tentang produk tersebut.…”
Section: Tabel 1 Top Brand Index (Tbi) Kosmetik Halal DI Indonesia Ta...unclassified